Saridin Mokong Karya Sucipto Hadi Purnomo Sebagai Respons Pembaca - Jannah, Raundoh Tul; Nugroho, Yusro Edy (Sutasoma : Jurnal Sastra Jawa, 2021)
Saridin Mokong is a Javanese serialized story of the Pati dialect resulting from literary reactualization from several sources such as Sri Kencono's Audio Kethoprak, the "Saridin Andhum Waris" culture from 1980-1990, Serat Syeh Jangkung, and Serat Babad Pati published in the Suara Merdeka Daily in 2008. However, the character's story legendary in the Pati regency region has never been studied the response of expert readers. Saridin Mokong, the work of Sucipto Hadi Purnomo as the Response of Expert Readers, is the latest research that raises reader responses as the main study. This research is expected to be able to find the acceptance and expectation horizons in the elements of character, plot, and background as facts and innovations with reference to narrative units from the three data sources. This study uses the diachronic literary reception method and the aesthetic theory of literary reception by Hans Robert Jauss with an intertextual approach. The results showed the expert reader response to the acceptance horizon of 10 out of 12 figures, 38 of the 41 narrative flow units, 11 of 13 backgrounds. Hope horizon of 14 characters, 66 units of flow narrative, 15 backgrounds. This means that the elements in the story are in the form of an expectation horizon or author's innovation more than the acceptance horizons of the three sources, Saridin Mokong by Sucipto Hadi Purnomo is a literary work that is different from Saridin's other works and does not come out from the standard elements so that the work is good and more liked by readers because it presents innovation according to the times. Furthermore, it is expected to be able to ignite cloud readers and implicitly give birth to innovation after the reading process. Keywords: expert reader response